Magnetic resonance imaging /ultrasonography fusion transperineal prostate biopsy for prostate cancer: Initial experience at a Middle Eastern tertiary medical centre. Issue 4 (2nd October 2021) - El-Achkar, Adnan; Al-Mousawy, Mouhammad; Abou Heidar, Nassib; Moukaddem, Hisham; Hussein, Hero; Mouallem, Nadim; El-Hajj, Albert; Bulbul, Muhammad
ABSTRACT: Objective : To report on the outcomes of magnetic resonance imaging (MRI)/ultrasonography (US)-fusion transperineal prostate (TP) biopsy at a tertiary medical centre in the Middle East including detection rate of clinically significant prostate cancer (csPCa), complications, and tolerability of the procedure. Patients and methods : Between May 2019 and June 2020, 98 MRI/US-fusion TP biopsies were performed in the US suite using light sedation. All patients had pre-biopsy 3-T multiparametric MRI. Data on patient characteristics, PCa detection rate and complication rates were collected retrospectively. A Gleason score ≥3 + 4 was defined as csPCa. Results: There were 98 patients, with a mean (SD) age of 65 (9.1) years, and a median (SD) prostate-specific antigen level prior to biopsy of 7.53 (12.97) ng/mL and prostate volume of 51 (31.1) mL. PCa was detected in 54 (55%) patients, with csPCa detected in 43 (44%). A total of 124 Prostate Imaging-Reporting and Data System (PI-RADS) 3–5 lesions were targeted. Grade Group ≥2 PCa was found in 35.5% of the targeted lesions. Random biopsies detected one csPCa Gleason score 3 + 4 in one patient with a negative target. None of the patients had post-biopsy haematuria or retention. Only one patient developed acute prostatitis requiring in-patient intravenous antibiotics. Conclusions: MRI/US-fusion TP biopsy has an adequate detection rate of csPCa with minimal complications and low infection rates after biopsy. This is one of the first TP biopsy series in the Middle East paving the way for wider adoption in the region. Abbreviations: AS: active surveillance; AUR: acute urinary retention; GG: Grade Group; IQR: interquartile range; mpMRI: multiparametric MRI; (cs)PCa: (clinically significant) prostate cancer; PI-RADS: Prostate Imaging-Reporting and Data System; TP: transperineal; US: ultrasonography; TRUS: transrectal Ultrasound guided.